Working Memory Capacity Does Not Always Support Future-Oriented Mind-Wandering. - McVay, Jennifer C.; Unsworth, Nash; McMillan, Brittany D.; Kane, Michael J. (Canadian Journal of Experimental Psychology / Revue Canadienne de Psychologie Expérimentale, 2013)
To evaluate the claim that mind-wandering demands executive resources, and more specifically that people with better executive control will have the resources to engage in more future-oriented thought than will those with poorer executive control, we reanalyzed thought-report data from 2 independently conducted studies (J. C. McVay & M. J. Kane, 2012, Why does working memory capacity predict variation in reading comprehension? On the influence of mind wandering and executive attention, Journal of Experimental Psychology: General, Vol. 141, pp. 302-320; N. Unsworth & B. D. McMillan, in press, Mind-wandering and reading comprehension: Examining the roles of working memory capacity, interest, motivation, and topic experience, Journal of Experimental Psychology: Learning, Memory, and Cognition) on working memory capacity (WMC), mind-wandering, and reading comprehension. Both of these individual-differences studies assessed large samples of university subjects' WMC abilities via multiple tasks and probed their immediate thought content while reading; in reporting any task-unrelated thoughts (TUTs), subjects indicated whether those thoughts were about the future or the past, if applicable. In contrast to previously published findings indicating that higher WMC subjects mindwandered about the future more than did lower WMC subjects (B. Baird, J. Smallwood, & J. W. Schooler, 2011, Back to the future: Autobiographical planning and the functionality of mind-wandering, Consciousness and Cognition, Vol. 20, pp. 1604-1611), we found only weak to modest negative correlations between WMC and future-oriented TUTs. If anything, our findings suggest that higher WMC subjects' TUTs were somewhat less often future-oriented than were lower WMC subjects'. Either WMC is not truly associated with mind-wandering about the future, or we have identified some important boundary conditions around that association.